The Effect of Astigmatism Aberration on Point Spread Function for Optical System Using Different Apertures - Hamza Tarkhan, Widad (Al-Qadisiyah Journal of Pure Science, 2018)
In this research , Point Spread Function (PSF) of an optical system has been studied, with a number of different apertures ( circular, square, rectangle (horizontal)). In case for diffraction limited system and with a different values of astigmatism aberration (W22=0.25 Î»,0.5 Î»,0.75 Î» and1 Î» ) and with different rotation angles (Ñ± = 0,45,90). The results showed that if the angle (Ñ± =0,45) is used, the rectangle (horizontal) aperture is the best in the distribution of intensity of the image plane and resolution power for optical system. While, The circular aperture was the best in decreasing the secondary peaks. When using the angle (Ñ±=90), and for all apertures, we observe the increasing of width of the function curve and increasing the secondary peaks, especially at (W22= 0.75 and 1). which effects negatively on the clarity image